The influence of gender on speech behavior (Journal of Pedagogical Inventions and Practices, 2023)
This article discusses the effect of gender differences on the speech of male and female speakers. The article examines various aspects of gender differences in speech, including lexical, phonetic, and semantic. The article is distinguished by the fact that gender differences are manifested in different ways and these aspects can be interpreted in the form of a unified structure on the basis of generality.